Detennination of the levels of zearalenone residue in feeds and feedstuffs by high performance liquid chromatography - Ahmet ACET; Ömer DEMET; Nesrin TUNCER; Behiç COŞKUN; Bünyamin TRAŞ; H. Hüseyin AĞAÇDELEN (Eurasian Journal of Veterinary Sciences)
The levets of zea.ralenone were investigated in total 99 various cornmerical fced mixtures and feed ingredients by using HPLC. The sensitivity of the method was found as 1 µg/kg. were eollected in tıhe periods of January - February and April - May from Konya, Adana, Bursa regions. In the first period, total 65 sampleıs which are 19 feeds and 46 feedstuffs were analysed. Zearnlenone was determine in 6 samples of tlhe feeds aınd 15 samples of the feedstuffs. The avarage level of zearalenone was calculated as 3.66 µg/kg in whole samples. In the second period, total 34 samples which are 11 feeds and 23 feedstuffs were analysed. Zearalenone was determined in 6 sampleıs of the feeds and 8 samples of tıhe feedstufıfs. The average level of zearalenone was caleulated as 5.46 µg/kg in whole samples. In both periods, the percentage of the samples included zearalenon was average 33 % and the mean zearalenone level was determined as 4.31 µg/kg feed. The samples contained about 10 µg/kg zearalenone may cause hipercostrogenism in pigs. Same effects mıay be seen in the other animals when these feedstuffs fed for a long periods.